Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x+y+z=3\Rightarrow x^2+y^2+z^2+2\left(xy+yz+zx\right)=9\Leftrightarrow xy+yz+zx=0\left(\text{vì:}x^2+y^2+z^2=9\right)\)
\(xy+yz+zx=0\Rightarrow xy=-yz-zx;yz=-xy-xz;xz=-xy-yz\)
\(P=\frac{-x\left(y+z\right)}{x^2}+\frac{-y\left(z+x\right)}{y^2}+\frac{-z\left(x+y\right)}{z}-4=\frac{y+z}{-x}+\frac{z+y}{-y}+\frac{x+y}{-z}-4\)
\(P=\frac{3}{x}+\frac{3}{y}+\frac{3}{z}-1=\frac{3yz+3xz+3xy}{xyz}-1=0-1=-1\)
a, Đặt \(A=16x^2-24x+9\)
⇒ \(A=(4x-3)^2\)
Vs x = 0
=> A = \((-3)^2=9\)
Vs \(x=\frac{1}{4}\)
⇒ \(A=\left(1-3\right)^2=4\)
Vs \(x=12\)
=> \(A=\left(48-3\right)^2=45^2=2025\)
Vs \(x=\frac{3}{4}\)
⇒ A = 0
2.
a, \(=4x^2-12x+9\)
b, \(=\frac{25}{16}-\frac{5}{2}x+x^2\)
c, \(=4x^2+12xy+9y^2\)
d, \(=9x^2+4xyz+\frac{4}{9}y^2z^2\)
e, \(=\left(\frac{x^2y^2}{4}-\frac{x^2y^2}{9}\right)\) (bỏ ngoặc hộ mình nhé <3)
f, \(=4x^2+y^2+z^2-4xy+4xz-2yz\)
- x.y=-2; xz=3 =>x2yz=-2.3=-6
=>x2=\(\frac{-6}{yz}\) = -6/-4=2/3
- xz=3;yz=-4 => z2xy=3.-4=-12
=> z2=-12/xy=-12/-2=6
- xy=-2;yz=-4=>y2xz=-2.-4=8
=>y^2=8/xz=8/-4=-2
====>x2+y2+z2=2/3+6-2=14/3